Chronic Unpredictable Mild Stress in Rats Induces Colonic Inflammation - Wei, Lina; Li, Ye; Tang, Wenjun; Sun, Qian; Chen, Lixin; Wang, Xia; Liu, Qingyi; Yu, Siqi; Yu, Shuyan; Liu, Chuanyong; Ma, Xuelian (Frontiers in Physiology, 2019)
Chronic psychological stress is associated with an increased risk for relapse of inflammatory bowel diseases (IBD) and impedes the treatment of this condition. However, the impact of stress on the risk of IBD onset remains unclear. The goal of the present study was to examine whether chronic unpredictable mild stress (CUMS) could initiate or aggravate the onset of colon inflammation in rats which, in turn, would be capable of triggering bowel disease. We found that CUMS exposure increased infiltration of CD-45 positive cells and MPO activity, as well as augmented the expression of the inflammatory cytokines, IFN γ and IL-6 within the colon of these rats. In addition, CUMS treatment changed the composition and diversity of gut microbiota and enhanced intestinal epithelial permeability, indicating the presence of a defect in the intestinal barrier. This CUMS-induced disruption of mucosal barrier integrity was associated with a reduction in expression of the tight junction protein, occludin 1, and an inhibition in mucosal layer functioning via reductions in goblet cells. Results from bacterial cultures revealed an increased presence of bacterial invasion after CUMS treatment as compared with that observed in controls. Thus, our data indicate that CUMS treatment induces alterations of the fecal microbiome and intestinal barrier defects, which facilitates bacterial invasion into colonic mucosa and further exacerbates inflammatory reactions within the colon. Accordingly, chronic stress may predispose patients to gastrointestinal infection and increase the risk of inflammation-related gut diseases.